A Possible Way to Encourage Sustainable Consumption - Karcagi-Kováts, Andrea; Szemerédi, Eszter (International Journal of Engineering and Management Sciences, 2019)
With the growth and spread of the concept of sustainable consumption and with the re-emergence of issues related to needs, the basic concepts of consumption need to be analyzed from aspects not inspected by mainstream economics. Consumer behaviour is largely determined by the prevailing values of society and nowadays consumption symbolizes social status. The purpose of this study is to critically examine the concept of utility, to review traditional and alternative concepts and aspirations related to the promotion of sustainable consumption. The authors argue, that utility can not only be examined by narrow economic considerations; the values of present and future generations also must be taken into account when determining what is considered to be useful. The study concludes by presenting alternative financial solutions that encourage sustainable consumption. The presented examples demonstrate, that complementary currency models are suitable means to encourage sustainable consumer behaviour. These are external motivational tools eliciting the desired behaviour through reward schemes.